Staffing the principalship : finding, coaching, and mentoring school leaders - Lovely, Suzette, 1958- 4 0 16; 5 Association for Supervision and Curriculum Development (Alexandria, Virginia : Association for Supervision and Curriculum Development, 2004)
Discusses the reasons for the shortage of principals anticipated by school districts around the U.S. in the near future, and offers advice on how to find high-quality candidates for principal positions from the ranks of teacher leaders and other applicants.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; In-service training;Recruiting;Job satisfaction;In-service training.;Recruiting. -- School principals;School principals;School principals;Mentoring in education;School superintendents and principals;School superintendents and principals;School superintendents and principals;Mentoring in education. -- United States.;United States.;United States.;United States.;United Staes;United States;United States; 20; 2